Josephson currents in point contacts between dirty two-band superconductors - Yerin, Y.S.; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We developed microscopic theory of Josephson effect in point contacts between dirty two-band superconductors. The general expression for the Josephson current, which is valid for arbitrary temperatures, is obtained. This expression was used for calculation of current-phase relations and temperature dependences of criticalcurrent with application to MgB2 superconductor. Also we have considered influence on contactcharacteristics interband scattering effect appeared in case of dirty superconductors. It is shown that the correction to Josephson current due to the interband scattering depends on phase shift in the banks (i.e., s- or s±-wave symmetry of order parameters).